Kinase crystal identification and ATP‐competitive inhibitor screening using the fluorescent ligand SKF86002. (1st February 2014) - Parker, Lorien J.; Taruya, Shigenao; Tsuganezawa, Keiko; Ogawa, Naoko; Mikuni, Junko; Honda, Keiko; Tomabechi, Yuri; Handa, Noriko; Shirouzu, Mikako; Yokoyama, Shigeyuki; Tanaka, Akiko
<x xml:space="preserve">Abstract</x> The small kinase inhibitor SKF86002 lacks intrinsic fluorescence but becomes fluorescent upon binding to the ATP‐binding sites of p38 mitogen‐activated protein kinase (p38α). It was found that co‐crystals of this compound with various kinases were distinguishable by their strong fluorescence. The co‐crystals of SKF86002 with p38α, Pim1, ASK1, HCK and AMPK were fluorescent. Addition of SKF86002, which binds to the ATP site, to the co‐crystallization solution of HCK promoted protein stability and thus facilitated the production of crystals that otherwise would not grow in the apo form. It was further demonstrated that the fluorescence of SKF86002 co‐crystals can be applied to screen for candidate kinase inhibitors. When a compound binds competitively to the ATP‐binding site of a kinase crystallized with SKF86002, it displaces the fluorescent SKF86002 and the crystal loses its fluorescence. Lower fluorescent signals were reported after soaking SKF86002–Pim1 and SKF86002–HCK co‐crystals with the inhibitors quercetin, a quinazoline derivative and A‐419259. Determination of the SKF86002–Pim1 and SKF86002–HCK co‐crystal structures confirmed that SKF86002 interacts with the ATP‐binding sites of Pim1 and HCK. The structures of Pim1–SKF86002 crystals soaked with the inhibitors quercetin and a quinazoline derivative and of HCK–SKF86002 crystals soaked with A‐419259 were determined. These structures were virtually identical to the deposited crystal structures of the same complexes. A KINOMEscan assay revealed that SKF86002 binds a wide variety of kinases. Thus, for a broad range of kinases, SKF86002 is useful as a crystal marker, a crystal stabilizer and a marker to identify ligand co‐crystals for structural analysis.